Negative electrode material and preparation method thereof, negative electrode plate and battery

By introducing carbon fine powder in the negative electrode material of lithium ion batteries, the problem of decreased lithium ion embedding/dehydration efficiency is solved, the battery high -temperature cycle performance and fast charging performance are improved, the cycle life of the battery is extended, and the cycle life of the battery is extended, and the cycle life of the battery is extended, and the cycle life of the battery is extended, and the cycle life of the battery is extended, and the cycle life of the battery is extended, and the cycle life of the battery is extended. Heat stability and safety.

CN119361661AActive Publication Date: 2025-01-24SHENZHEN HIGHPOWER TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411911337.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-01-24
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The negative electrode materials of existing lithium-ion batteries exhibit problems such as reduced lithium-ion embedding/deintercalation efficiency, accelerated SEI film reconstruction, and intensified volume expansion at high temperatures, resulting in a shortened battery cycle life, reduced thermal stability and increased safety risks.

Method used

A negative electrode material is composed of carbon particles A, carbon particles B and carbon fine powder. The particle size of the carbon fine powder is ≤2 μm, the number content is 20%~ 40%, and the volume content is 0.1%to 2%. This material is prepared and grained technology preparation to ensure the distribution and role of carbon fine powder in the material.

Benefits of technology

By increasing the surface area of ​​carbon fine powder, the structure of the negative material is optimized, the high temperature cycle performance and fast charge performance of the material are improved, the cycle life of the battery is prolonged, and the thermal stability and safety of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361661A_ABST
    Figure CN119361661A_ABST
Patent Text Reader

Abstract

In order to solve the problem that in the prior art, the fast charging performance and the high-temperature performance of a graphite material cannot be guaranteed at the same time, the invention provides a negative electrode material, a preparation method thereof and a battery, the negative electrode material comprises carbon particles a, carbon particles b and carbon fine powder, the carbon particles a, the carbon particles b and the carbon fine powder are all graphitized carbon materials, the carbon particles a are secondary particles, and the carbon particles b are secondary particles. The carbon particles b are single particles; the particle size of the carbon fine powder is less than or equal to 2 microns; in the negative electrode material, the quantity content of the carbon fine powder is 20%-40%, and the volume content of the carbon fine powder is 0.1%-2%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a negative electrode material and a preparation method thereof, a negative electrode sheet, and a battery. Background Art

[0002] Lithium-ion batteries are developing rapidly and are widely used in various electronic products. They have higher requirements for performance, especially stability and safety under extreme temperature conditions. Under high temperature environment, the negative electrode materials of traditional lithium-ion batteries, such as artificial graphite and natural graphite, will have serious problems such as reduced lithium ion insertion / extraction efficiency, accelerated SEI film reconstruction, and increased volume expansion at high temperature (≥60°C), which will lead to shortened battery cycle life, reduced thermal stability and increased safety hazards. At present, the solutions to improve the high-temperature performance of materials are mainly: (1) using needle coke and calcined needle coke with less volatiles as raw materials; (2) increasing the graphite particle size; (3) reducing the functional groups on the graphite surface; (4) optimizing the material structure. Among these solutions, using needle coke and calcined needle coke with less volatiles as raw materials is the main strategy currently expected by downstream companies. In order to further improve the high-temperature performance, if the graphite particle size is increased under the premise of using the above raw materials, the fast charging performance of artificial graphite materials will decrease. Therefore, it is urgent to ensure the fast charging performance of materials while improving the high-temperature performance requirements of modified graphite materials. Summary of the invention

[0003] In view of the problem that the prior art cannot simultaneously ensure the fast charging performance and high temperature performance of graphite materials, the present invention provides a negative electrode material and a preparation method thereof, a negative electrode sheet, and a battery.

[0004] The technical solution adopted by the present invention to solve the above technical problems is as follows: In a first aspect, the present invention provides a negative electrode material, including carbon particles a, carbon particles b and carbon fine powder, wherein the carbon particles a, carbon particles b and carbon fine powder are all graphitized carbon materials, the carbon particles a are secondary particles, and the carbon particles b are single particles; the particle size of the carbon fine powder is ≤2 μm; In the negative electrode material, the amount content of the carbon fine powder is 20% to 40%, and the volume content of the carbon fine powder is 0.1% to 2%.

[0005] Optionally, in the negative electrode material, the amount content of the carbon fine powder is 28%~32%, and the volume content of the carbon fine powder is 0.2%~0.7%.

[0006] Optionally, the number ratio of the carbon particles a to the carbon particles b is (50-70): (30-50).

[0007] Optionally, the negative electrode material satisfies the following relationship: 5≤Dv50 / Dn50≤6, Dv50 is the volume median particle size of the negative electrode material, and Dn50 is the number median particle size of the negative electrode material.

[0008] Optionally, the Dv50 is 12~16μm, and the Dn50 is 2~3.2μm.

[0009] Optional, 5.3≤Dv50 / Dn50≤5.6.

[0010] Optionally, the carbon particles a, carbon particles b and carbon fine powder are each independently selected from one or more of artificial graphite, natural graphite and composite graphite; And / or, the compaction density of the negative electrode material is greater than 1.75 g / cc, and the gram capacity is greater than 356 mAh / g.

[0011] In a second aspect, the present invention provides a method for preparing a negative electrode material as described in any one of the above, comprising the following steps: The graphite raw material is crushed and graphitized to obtain a graphitized carbon material; Screening the graphitized carbon material to obtain carbon fine powder and carbon particles b; Using asphalt to perform secondary granulation on a portion of the carbon particles b to obtain carbon particles a; The carbon particles a, carbon particles b and carbon fine powder are mixed to obtain a negative electrode material.

[0012] In a third aspect, the present invention provides a negative electrode sheet, comprising a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises the negative electrode material as described in any one of the above items, or comprises the negative electrode material prepared by the above-described preparation method.

[0013] In a fourth aspect, the present invention provides a battery comprising the negative electrode sheet as described above.

[0014] In the present invention, the negative electrode material containing carbon fine powder particles, when meeting the relationship that the particle size of carbon fine powder is ≤2μm, the quantity content of carbon fine powder is 20%~40%, and the volume content of carbon fine powder is 0.1%~2%, benefits from the large specific surface area of ​​carbon fine powder, and in the process of forming negative electrode slurry of negative electrode material, too much binder is occupied, so that the content of binder on the surface of other large particle size particles (such as carbon particles a and carbon particles b) is less, and since the carbon fine powder has a small particle size and good dynamic performance, the surface binder will not deteriorate the dynamic performance of the material, and can also play the effect of bonding large particles in the negative electrode sheet. At the same time, the carbon fine powder is filled in the gap between carbon particles a and carbon particles b, which can further improve the use compaction of the negative electrode material. The presence of carbon particles a and carbon particles b during the charging and discharging process of the battery makes the battery interface polarization smaller, improves the surface polarization of the negative electrode material, shortens the charging time under high temperature cycle, and improves the high temperature standing time under high voltage, thereby improving the high temperature cycle of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a SEM image of a negative electrode material provided by one embodiment of the present invention. DETAILED DESCRIPTION

[0016] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0017] An embodiment of the present invention provides a negative electrode material, including carbon particles a, carbon particles b and carbon fine powder, wherein the carbon particles a, carbon particles b and carbon fine powder are all graphitized carbon materials, the carbon particles a are secondary particles, and the carbon particles b are single particles; the particle size of the carbon fine powder is ≤2 μm; In the negative electrode material, the amount content of the carbon fine powder is 20% to 40%, and the volume content of the carbon fine powder is 0.1% to 2%.

[0018] In the present invention, the negative electrode material containing carbon fine powder particles, when satisfying the relationship that the particle size of carbon fine powder is ≤2μm, the quantity content of carbon fine powder is 20%~40%, and the volume content of carbon fine powder is 0.1%~2%, benefits from the large specific surface area of ​​carbon fine powder, and in the process of forming negative electrode slurry of negative electrode material, too much binder is occupied, so that the content of binder on the surface of other large particle size particles (such as carbon particles a and carbon particles b) is less, and since the carbon fine powder has a small particle size and good dynamic performance, the binder on the surface will not deteriorate the dynamic performance of the material, and can also play the effect of bonding large particles in the negative electrode sheet. At the same time, the carbon fine powder is filled in the gap between carbon particles a and carbon particles b, which can further improve the compaction of the negative electrode material. The presence of carbon particles a and carbon particles b during the charging and discharging process of the battery makes the battery interface polarization smaller, improves the surface polarization of the negative electrode material, shortens the charging time under high temperature cycle, and improves the high temperature standing time under high voltage, thereby improving the high temperature cycle of the material.

[0019] Specifically, the amount of carbon fine powder includes but is not limited to 20%, 23%, 26%, 29%, 32%, 35%, 38% or 40%.

[0020] The volume content of the carbon fine powder includes, but is not limited to, 0.1%, 0.3%, 0.6%, 0.9%, 1.2%, 1.5%, 1.8% or 2%.

[0021] In a preferred embodiment, in the negative electrode material, the amount of the carbon fine powder is 28% to 32%, and the volume content of the carbon fine powder is 0.2% to 0.7%. In the negative electrode material, the carbon fine powder within the above amount and volume content range can further improve the high temperature performance of the battery while ensuring its fast charging performance.

[0022] In some embodiments, the mass ratio of the carbon particles a to the carbon particles b is (50-70): (30-50).

[0023] In some embodiments, the negative electrode material satisfies the following relationship: 5≤Dv50 / Dn50≤6, Dv50 is the volume median particle size of the negative electrode material, and Dn50 is the number median particle size of the negative electrode material. When the negative electrode material satisfies the above relationship, the carbon fine powder is filled in the gaps between the carbon particles a and the carbon particles b, and the negative electrode material composed of the particles a, the carbon particles b and the carbon fine powder can improve the use compaction of the negative electrode material and improve the surface polarization of the negative electrode material.

[0024] Specifically, the value of Dv50 / Dn50 includes but is not limited to 5, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9 or 6.

[0025] In some embodiments, the Dv50 is 12-16 μm, and the Dn50 is 2-3.2 μm. By selecting the negative electrode material in the above particle size range, the negative electrode material has a higher compaction density.

[0026] In a preferred embodiment, 5.3≤Dv50 / Dn50≤5.6. When the negative electrode material satisfies the above relationship, the use compaction of the negative electrode material can be further improved, and the surface polarization of the negative electrode material can be improved.

[0027] In some embodiments, the carbon particles a, carbon particles b and carbon fine powder are each independently selected from one or more of artificial graphite, natural graphite and composite graphite.

[0028] In some embodiments, the compaction density of the negative electrode material is greater than 1.75 g / cc, and the gram capacity is greater than 356 mAh / g, so as to increase the energy density of the battery and improve the fast charging performance of the battery.

[0029] An embodiment of the present invention provides a method for preparing a negative electrode material as described above, comprising the following steps: The graphite raw material is crushed and graphitized to obtain a graphitized carbon material; specifically, the average volume particle size D50 of the crushed graphite raw material is 6-12 μm.

[0030] Screening the graphitized carbon material to obtain carbon fine powder and carbon particles b; Part of the carbon particles b is subjected to secondary granulation treatment using asphalt to obtain carbon particles a; specifically, the average volume particle size D50 of the carbon particles a after secondary granulation is 12-16 μm.

[0031] The carbon particles a, carbon particles b and carbon fine powder are mixed to obtain a negative electrode material.

[0032] An embodiment of the present invention provides a negative electrode sheet, comprising a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises the negative electrode material as described in any one of the above items, or comprises the negative electrode material prepared by the above-described preparation method.

[0033] An embodiment of the present invention provides a battery, comprising the negative electrode sheet as described above.

[0034] The present invention is further described below by way of examples.

[0035] Example 1

[0036] This embodiment is used to illustrate the electrode and battery disclosed in the present invention, and includes the following operating steps: Preparation of negative electrode materials: The graphite of the coke raw material is crushed, and the particle size D50 of the crushed coke raw material aggregate is 6~12μm, and then graphitization processing is carried out. The graphitized carbon material is screened with sieves of different meshes, and the carbon fine powder with a particle size of ≤2μm is screened out. Then, part of the carbon particles b in the remaining material are granulated with asphalt for secondary particles. The particle size D50 of the carbon particles after granulation is 12~16μm. The graphitized secondary particles, graphitized single particles, and graphitized carbon fine powder are physically mixed to obtain the negative electrode material. Among them, the number content W of the carbon fine powder is 30%, the volume content V of the carbon fine powder is 0.5%, the Dv50 of the negative electrode material is 14μm, the Dn50 is 2.55μm, and the Dv50 / Dn50 is 5.5. The mass ratio of carbon particles a and carbon particles b is 60:40.

[0037] Negative electrode sheet: The negative electrode material, conductive carbon black SP, CMC and SBR are mixed in a proper amount of deionized water solvent at a mass ratio of 95.5:1.0:1.5:2.0 to form a uniform negative electrode slurry. The slurry is evenly coated on the negative electrode current collector Cu foil, vacuum dried in a vacuum drying oven at 110℃ for 6 hours, and cold pressed to obtain the negative electrode sheet. Positive electrode: The positive electrode active material lithium cobalt oxide, the conductive agent CNT, and the adhesive PVDF are fully stirred and mixed in NMP solvent at a weight ratio of 97:1.5:1.5, and the slurry is coated on aluminum foil. After drying, cold pressing, slitting, sheeting, welding of pole ears, and gluing, a positive electrode sheet that meets the requirements is made.

[0038] Lithium-ion battery production: Stack the positive electrode sheet, separator and negative electrode sheet in order, so that the separator is in the middle of the positive and negative electrodes to play a role of isolation, and then wind it into a bare cell. Put the bare cell in an outer packaging bag, inject the prepared electrolyte into the dried battery, and complete the battery preparation through vacuum packaging, static, formation, shaping and other processes.

[0039] Example 2-12 The embodiment is used to illustrate the electrode and battery disclosed in the present invention, including most of the operating steps in Example 1, and the difference is that: the formula in Table 1 is used.

[0040] Comparative Examples 1-8 The comparative example is used to compare and illustrate the electrode and battery disclosed in the present invention, and includes most of the operating steps in Example 1, except that the formula in Table 1 is used.

[0041] Table 1

[0042] Performance Testing 1. The batteries prepared in the above examples and comparative examples were subjected to the following performance tests: 1. Cycle stability test: Place the battery in a 45±2℃ environment for 4 hours, and cycle it for 400 cycles according to the standard charge and discharge cycle, with a cycle rate of 1C / 1C and a voltage of 3.0-4.4V. Calculate the capacity retention rate of the battery after the cycle. The calculation formula is as follows: The capacity retention rate of the nth cycle (%) = (discharge capacity of the nth cycle) / (discharge capacity of the first cycle) * 100%.

[0043] 2. The charging time is the constant current time + constant current and constant voltage time during the charging process.

[0044] The test results are shown in Table 2.

[0045] Table 2

[0046] Depend on Figure 1 It can be seen that the negative electrode material contains carbon particles a, carbon particles b and carbon fine powder.

[0047] From the test results of Example 1 and Comparative Example 1 in Table 2, it can be seen that the inclusion of fine carbon powder in the negative electrode material can improve the high temperature cycle of the material and shorten the charging time under high temperature cycle. From the test results of Examples 1 to 6 and Comparative Examples 2 to 4, 7, and 8, it can be seen that when the amount content of fine carbon powder is 28% to 32% and the volume content of fine carbon powder is 0.3% to 0.7%, the battery has a good capacity retention rate at 45°C.

[0048] From the test results of Examples 1, 7-12, Comparative Examples 5 and 6, it can be seen that the negative electrode material obtained by using carbon particles a alone or carbon particles b mixed with carbon fine powder has a longer charging time at high temperature. If the negative electrode material obtained by mixing carbon particles b with carbon fine powder is used, the compaction of the obtained pole piece fails to reach 1.75g / cc, further affecting the energy density of the battery. When the mass range of carbon particles a and carbon particles b in the negative electrode material is in the range of (50-70): (30-50), and the Dv50 / Dn50 of the negative electrode material is in the range of 5-6, the battery has a shorter charging time under high temperature cycles.

[0049] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A negative electrode material, characterized in that: It comprises carbon particles a, carbon particles b and carbon fine powder, wherein the carbon particles a, carbon particles b and carbon fine powder are all graphitized carbon materials, the carbon particles a are secondary particles, and the carbon particles b are single particles; the particle size of the carbon fine powder is ≤2 μm; In the negative electrode material, the amount content of the carbon fine powder is 20% to 40%, and the volume content of the carbon fine powder is 0.1% to 2%.

2. The negative electrode material according to claim 1, characterized in that In the negative electrode material, the amount content of the carbon fine powder is 28% to 32%, and the volume content of the carbon fine powder is 0.2% to 0.7%.

3. The negative electrode material according to claim 1, characterized in that The mass ratio of the carbon particles a to the carbon particles b is (50-70): (30-50).

4. The negative electrode material according to claim 1, characterized in that The negative electrode material satisfies the following relationship: 5≤Dv50 / Dn50≤6, Dv50 is the volume median particle size of the negative electrode material, and Dn50 is the number median particle size of the negative electrode material.

5. The negative electrode material according to claim 4, characterized in that The Dv50 is 12~16μm, and the Dn50 is 2~3.2μm.

6. The negative electrode material according to claim 4, characterized in that 5.3≤Dv50 / Dn50≤5.

6.

7. The negative electrode material according to claim 1, characterized in that The carbon particles a, carbon particles b and carbon fine powder are independently selected from one or more of artificial graphite, natural graphite and composite graphite; And / or, the compaction density of the negative electrode material is greater than 1.75 g / cc, and the gram capacity is greater than 356 mAh / g.

8. A method for preparing a negative electrode material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The graphite raw material is crushed and graphitized to obtain a graphitized carbon material; Screening the graphitized carbon material to obtain carbon fine powder and carbon particles b; Part of the carbon particles b are subjected to secondary particle granulation treatment using asphalt to obtain carbon particles a; the carbon particles a, carbon particles b and carbon fine powder are mixed to obtain negative electrode materials.

9. A negative electrode sheet, characterized in that: It comprises a current collector and an active material layer arranged on at least one side of the current collector, wherein the active material layer comprises the negative electrode material according to any one of claims 1 to 7, or comprises the negative electrode material prepared by the preparation method according to claim 8.

10. A battery, characterized in that: Includes the negative electrode sheet as described in claim 9.

Citation Information

Patent Citations

  • High capacity and high magnification composite graphite material for lithium ion battery and preparation method thereof

    CN105244485A

  • Graphene-based composite anode material and preparation method thereof and lithium ion battery

    CN110970599A

  • Graphite material and preparation method thereof, negative plate and lithium ion battery

    CN113871601A

  • Lithium ion battery carbon negative electrode material and preparation method and system thereof

    CN114864906A

  • Negative pole piece and preparation method thereof, battery and vehicle

    CN116344743A